Estudo das propriedades elétricas, ópticas e morfológicas da blenda polimérica de PEDOT:PSS e Nanofios de prata - Pavan, Havena Louise (2023)
Poly(3,4-ethylenedioxythiophene) doped with poly(styrenesulfonated), known as PEDOT:PSS, is a polymeric blend commonly used as a conductive electrode or conductive layer in photovoltaic devices. In this study, techniques were proposed to increase the conductivity of PEDOT:PSS through association with layers of silver nanowires (AgNWs) or incorporation in a dimethyl sulfoxide (DMSO) solution. PEDOT:PSS was processed into thin films on polyethylene terephthalate (PET) substrates, using the spin-coatig technique, serving as a flexible and low-cost alternative to indium tin oxide (ITO). The sheet resistance of the pure PEDOT:PSS film is approximately 70kΩ/sq, and could be reduced to less than 30 Ω/sq. The tests resulted in PEDOT:PSS/AgNWs films, with sheet resistance of 32 Ω/sq and transmittance of 78 %, produced from the mixture of PEDOT:PSS : DMSO: deionized water: ethanol, with addition of 1 layer of AgNWs. For the film deposited in the inverted order, AgNWs/PEDOT:PSS, sheet resistance reduction techniques were also applied based on exposure to HCl vapor, deposition of AgNO3 or deposition of acidic solution. These films produced in the inverted order AgNWs/PEDOT:PSS, despite showing less adhesion to the PET substrate, had a reduction of approximately 20% in sheet resistance, compared to films from PEDOT:PSS/AgNWs. The results obtained were promising for application in optoelectronic devices, since the figure of merit (FoM) of the film produced is equivalent with the commercial materials.